Hepatic stellate cell-intrinsic role of SOCS1 in controlling hepatic fibrogenic response and the pro-inflammatory macrophage compartment during liver fibrosis - Kandhi, Rajani; Yeganeh, Mehdi; Yoshimura, Akihiko; Menendez, Alfredo; Ramanathan, Sheela; Ilangumaran, Subburaj (Frontiers in Immunology, 2023)
Introduction Hepatic stellate cells (HSC) become activated, differentiate to myofibroblasts and produce extracellular fibrillar matrix during liver fibrosis. The hepatic fibrogenic response is orchestrated by reciprocal interactions between HSCs and macrophages and their secreted products. SOCS1 can regulate several cytokines and growth factors implicated in liver fibrosis. Here we investigated the role of SOCS1 in regulating HSC activation. Methods Mice lacking SOCS1 in HSCs (Socs1ΔHSC) were generated by crossing Socs1fl/fl and LratCre mice. Liver fibrosis was induced by carbon tetrachloride and evaluated by Sirius red staining, hydroxyproline content and immunostaining of myofibroblasts. Gene expression of pro-fibrogenic factors, cytokines, growth factors and chemokines were quantified by RT-qPCR. The phenotype and the numbers of intrahepatic leukocyte subsets were studied by flow cytometry. The impact of fibrosis on the development of diethyl nitrosamine-induced hepatocellular carcinoma was evaluated. Results Socs1ΔHSC mice developed more severe liver fibrosis than control Socs1fl/fl mice that was characterized by increased collagen deposition and myofibroblast differentiation. Socs1ΔHSC mice showed a significant increase in the expression of smooth muscle actin, collagens, matrix metalloproteases, cytokines, growth factors and chemokines in the liver following fibrosis induction. The fibrotic livers of Socs1ΔHSC mice displayed heightened inflammatory cell infiltration with increased proportion and numbers of Ly6ChiCCR2+ pro-inflammatory macrophages. This macrophage population contained elevated numbers of CCR2+CX3CR1+ cells, suggesting impaired transition towards restorative macrophages. Fibrosis induction following exposure to diethyl nitrosamine resulted in more numerous and larger liver tumor nodules in Socs1ΔHSC mice than in Socs1fl/fl mice. Discussion Our findings indicate that (i) SOCS1 expression in HSCs is a critical to control liver fibrosis and development of hepatocaellular carcinoma, and (ii) attenuation of HSC activation by SOCS1 regulates pro-inflammatory macrophage recruitment and differentiation during liver fibrosis.